The stability and growth pact, and balanced budget fiscal stimulus: Evidence from Germany and Italy - Konstantinos Karagounis; Dimitrios Syrrakos; John Simister (Intereconomics, 2015)
This paper assesses the limitations that the Stability and Growth Pact has imposed on Italy's economic recovery and its debt reduction. By evaluating Germany's fiscal policy since 1997, the paper offers recommendations for the Italian authorities. Measures put forward by European Union institutions are hampering Italy's economic recovery, and evidence indicates that fiscal consolidation is ineffective in reducing the debt-to-GDP ratio. A balanced budget fiscal injection seems the only way for Italy to escape from its economic slump without further violations of the SGP. The paper concludes that the Pact either needs to be reformed or replaced by a central fiscal authority.
Keywords: 330; Europäischer Stabilitätsmechanismus; Wirtschaftliche Anpassung; Wirkungsanalyse; Systemvergleich; Deutschland; Italien